An improved classification of foci for carcinogenicity testing by statistical descriptors. Issue 7 (October 2015) - Callegaro, Giulia; Stefanini, Federico Mattia; Colacci, Annamaria; Vaccari, Monica; Urani, Chiara
Graphical abstract